Women and Judaism: new insights and scholarship - Greenspahn, Frederick E. (Jewish studies in the 21st century, 2009)
Four approaches to women and the Jewish experience / Judith R. Baskin -- Jewish feminist approaches to the bible / Esther Fuchs -- Women and Torah study in aggadah / Dvora E. Weisberg -- Women and Jewish law / Judith Hauptman -- Women in medieval Jewish societies / Renée Levine Melammed -- The mystical spirituality of eastern European Jewish women / Chava Weissler -- How central European Jewish women confronted modernity / Harriet Pass Freidenreich -- Women and American Judaism / Pamela S. Nadell -- Women's transformations of contemporary Jewish life / Sylvia Barack Fishman -- Women in Jewish American literature / Sara R. Horowitz -- Text, nation, and gender in Israeli women's fiction / Nehama Aschkenasy -- Women and Judaism : from invisibility to integration / Frederick E. Greenspahn